The influence of administrative services, medical services, and drug availability on the level of outpatient satisfaction moderated by waiting time - Catalya Christina Cantika; Hery Winoto TJ; Melitina Tecoalu (Junal Ilmu Manajemen, 2023)
Customer satisfaction is the key to creating customer loyalty, as are the services at hospitals, which include administrative services, medical services, drug availability, and patient waiting times when visiting the hospital. This study will examine aspects of administrative services, medical services, and drug availability and their influence on patient satisfaction, with waiting time as a moderating variable, at Pakuhaji Hospital, Tangerang Regency. The research method was a descriptive study using a questionnaire instrument with a sample of 92 patients at Pakuhaji General Hospital, Tangerang Regency. The results showed that there was a positive and significant influence on administrative services (p=0,000), medical services (p=0,000), and drug availability (p=0,024) on patient satisfaction at Pakuhaji General Hospital, Tangerang Regency (α=0,05). Waiting time with questions, namely waiting time less than 60 minutes can be moderately administrative; waiting time for outpatient services less than 60 minutes can be moderately medical; and waiting time for laboratory examination results less than 30 minutes can be moderately medical at Pakuhaji Hospital, Tangerang Regency.